2021
DOI: 10.3390/microorganisms9112391
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Biological Activity of Vitis vinifera Winter Cane Extract on Candida Biofilm

Abstract: Vitis vinifera canes are waste material of grapevine pruning and thus represent cheap source of high-value polyphenols. In view of the fact that resistance of many pathogenic microorganisms to antibiotics is a growing problem, the antimicrobial activity of plant polyphenols is studied as one of the possible approaches. We have investigated the total phenolic content, composition, antioxidant activity, and antifungal activity against Candida biofilm of an extract from winter canes and a commercially available e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Kodešet al 177 evaluated the antifungal activity of cane extract against Candida biofilm formation. A decrease in cell adhesion to the surface depending on the concentration of resveratrol in the cane extract was reported.…”
Section: ■ Technofunctional Applicationsmentioning
confidence: 99%
“…Kodešet al 177 evaluated the antifungal activity of cane extract against Candida biofilm formation. A decrease in cell adhesion to the surface depending on the concentration of resveratrol in the cane extract was reported.…”
Section: ■ Technofunctional Applicationsmentioning
confidence: 99%
“…The cosmetic formulation was achieved by dissolving the Carbopol in a mixture of extract/water: 75%/17% ratio at room temperature, while to form a homogeneous gel, triethanolamine was added under continuous stirring. Furthermore, vine cane extracts effectively inhibit the formation of biofilm on Candida albicans and Candida parapsilosis strains, with a minimum inhibitory concentration (MIC) value of 5 mg/L and 30 mg/L respectively [ 70 ].…”
Section: Development Of Cosmetic Formulations Based On Bioactive Comp...mentioning
confidence: 99%
“…Data regarding the biological potential of the purified grapevine cane polyphenolic extracts are very scarce, most of the research being mainly directed at the identification and quantification of stilbenes, rather than to a synergistic valorization of the plant material composition. Recent studies have shown that grapevine cane crude extracts are rich in bioactive compounds with good antioxidant potential [38,39] and particular antimicrobial activity against different bacteria and yeasts [39,40], but the reported results vary widely depending on the grapevine genotype and the tested microorganisms, in generally being directly correlated with the phenolic compounds' concentration [4].…”
Section: Introductionmentioning
confidence: 99%